Bionanocomposites: Drug Delivery System: Enhancing Drug Delivery through Bionanocomposites (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The drug's solubility, subsequent transport through the intestinal membrane, and transitthrough the liver affect the pace of absorption and, therefore, the commencement of action. Thebioavailability and, finally, the solubility of a drug's molecules determine its therapeutic efficacy. Onecrucial factor in achieving the optimum medication concentration in the bloodstream so that apharmacological reaction may be seen is solubility. Only 8 of potential new drugs now in developmenthave good solubility and permeability. The low water solubility of many medications is a major obstacle tothe creation of highly effective formulations. When developing formulations, conducting clinical trials, orevaluating novel chemicals for medicinal efficacy, poor solubility is a concern. The bioavailability andabsorption of such novel chemical are constrained by poor water solubility. Methodical formulationapproaches are necessary to increase the bioavailability of such drugs due to their poor solubility. Suchmedications must have a high enough absorption rate after oral administration or be given intravenouslyin order to be considered bioavailable.